2020
DOI: 10.1007/s00262-020-02667-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of a T cell-dependent bispecific antibody as a breakthrough immunotherapy against refractory colorectal cancer with an oncogenic mutation

Abstract: T cell-dependent bispecific antibody (TDB)-induced T cell activation, which can eliminate tumor cells independent of MHC engagement, is expected to be a novel breakthrough immunotherapy against refractory cancer. However, the mechanism of action of TDBs has not been fully elucidated thus far. We focused on TDB-induced T cell-tumor cell contact as an important initial step in direct T cell-mediated tumor cell killing via transport of cytotoxic cell proteases (e.g., granzymes) with or without immunological synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…In an inhibition assay, Gruen and colleagues found that other death ligands in addition to the Fas-FasL pathway, including TRAIL and TNFα, also failed to cause T-BsAb-induced lysis of B-cell lines from leukemia and lymphoma [90]. Recently, however, we demonstrated that secreted cytokines from T-BsAb-activated T cells damaged target cells in a cell contact-independent manner, although cell contact-dependent tumor cell killing, which was presumably attributed to perforin and granzyme activity, showed stronger cytotoxicity [82]. This discrepancy might be explained by target cells having differing sensitivity to various ligands and cytokines.…”
Section: Local Mechanism Of Action Within Tumor Tissuesmentioning
confidence: 87%
See 1 more Smart Citation
“…In an inhibition assay, Gruen and colleagues found that other death ligands in addition to the Fas-FasL pathway, including TRAIL and TNFα, also failed to cause T-BsAb-induced lysis of B-cell lines from leukemia and lymphoma [90]. Recently, however, we demonstrated that secreted cytokines from T-BsAb-activated T cells damaged target cells in a cell contact-independent manner, although cell contact-dependent tumor cell killing, which was presumably attributed to perforin and granzyme activity, showed stronger cytotoxicity [82]. This discrepancy might be explained by target cells having differing sensitivity to various ligands and cytokines.…”
Section: Local Mechanism Of Action Within Tumor Tissuesmentioning
confidence: 87%
“…Further, these markers have been commonly detected in three types of ISs induced by T-BsAbs with different configurations, indicating that this might be a general pattern among T-BsAbs. Many studies have visualized T-BsAb-induced ISs in vitro [80][81][82]. Recently, IS formation was successfully evaluated by Cremasco et al in an in vivo humanized mouse model involving transfer of human hematopoietic stem cells [75].…”
Section: Local Mechanism Of Action Within Tumor Tissuesmentioning
confidence: 99%
“…In vitro , tebentafusp induced cell killing that led to cross-presentation of tumor antigen that could stimulate epitope spreading ( 5 ). In addition, T cells activated by TCE may release cytokines that kill adjacent, antigen negative tumor cells ( 6 ).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…One potential explanation is that tebentafusp, with in vitro sensitivity to very low pHLA/cell, may outstrip the sensitivity of IHC, requiring >10 3 molecules per cell. Alternatively, even a small percentage of gp100 + cells may be sufficient for tebentafusp to trigger an initial immune response that could result in IFN-induced upregulation ( 43 ), cytokine-mediated tumor stasis or killing ( 6 ), or epitope spreading ( 5 ). Finally, even a low percentage of positive tumor cells may be sufficient for tebentafusp to slow tumor growth kinetics.…”
Section: Clinical Validation With Tebentafusp In Mummentioning
confidence: 99%
See 1 more Smart Citation